First Kasadya-an [videorecoring] Leyte festival of festivals, Ormoc City, May 11-12, 1976 / National Commission for Culture and the Arts. - Philippines. National Commission for Culture and the Arts. (Manila NCCA, 1996)
A documentation of the festival. Also performances of the different cultural dances of the province of Leyte.
VHS.
Keywords: Kasadya-an Festival; Festivals -- Philippines -- Leyte